ANALISIS PENGARUH PERLAKUAN KAVITASI ULTRASONIK TERHADAP STRUKTUR MIKRO PADA DAUN TANAMAN NILAM (Pogostemon cublin benth) - Rezky Eko Bawono; Hendi Saryanto; Darwin Sebayang (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Essential oils are one of Indonesia's natural products that are widely used as the basic ingredients of medicines, perfumes, as flavor and food preservatives, aromatherapy, vegetable pepticides and so on. Raw materials for essential oils can be in the form of leaves, flowers, logs, bark, fruit seeds, roots or rhizomes. Essential oils in aromatic plants are found in oil glands, vessels, oil sacs or hair glands (grandular). The test uses the leaves of patchouli as a testing medium. To optimize the production of essential oils on patchouli leaves, prefix treatment is needed. This treatment is expected to help the process of macro and micro cell destruction. At the macro level, this cell destruction can be done by chopping or counting raw materials. However, for micro-cell destruction can be done by giving high waves to raw materials. In this case the intended waveform is an ultrasonic wave with 40 kHz. The variables compared in this study were ultrasonic treatment and the duration of treatment given. The first experiment compared the patchouli leaves that were exposed to ultrasonic and those that did not use ultrasonic. Then, the second experiment using ultrasonic for 15 minutes and 60 minutes. After the ultrasonic process is done, then using scanning electron microscopy to see the micro-structure of the leaves. The results of this study found that the leaf structure that was not subjected to ultrasonic treatment had a neater oil bag compared to those affected by ultrasonic. Further results were obtained that the ultrasonic duration also affected the micro-structure of the leaves